Carbohydrate microarrays fabricated on poly(2-methylacrylic acid)-based substrates for analysis of carbohydrate–protein interactions. (10th February 2022) - Liu, Chanjuan; Yang, Luyao; Niu, Qingfeng; Yu, Guangli; Li, Guoyun
Abstract : Carbohydrate microarrays were fabricated on poly(2-methylacrylic acid) (pMAA)-based substrates. They were used for investigating the specific interactions of polysaccharides and SARS-CoV-2 spike protein. Abstract : Carbohydrate microarrays, featuring high-throughput and rapid detection, provide a powerful tool for getting better insights into carbohydrate-mediated interactions. In this study, poly(2-methylacrylic acid) (pMAA)-modified substrates have been developed for fabricating carbohydrate microarrays. The abundant carboxyl groups of the pMAA polymer provide large amounts of reaction sites for subsequent carbohydrate immobilization. After the activation of the carboxyl groups, amino-modified carbohydrates were covalently and site-specifically immobilized on the pMAA-based substrates. As a typical example, the specific interaction between 4-aminophenyl α-d -mannopyranoside (α-Man) and fluorescein isothiocyanate labelled concanavalin A (ConA-FITC) was investigated using a pMAA-based carbohydrate microarray. It exhibited a low limit of detection of both spotted α-Man (10 μM) and ConA-FITC in solution (9.26 nM) without any further signal amplification. The practical application of the pMAA-based microarrays was validated by investigating the specific interactions of polysaccharides and SARS-CoV-2 spike protein, and fabricating microarrays containing other biomolecules ( e.g., glycoprotein and DNA). The proposed pMAA-based microarrays provide a promising tool in bioanalytical and biomedical studies.